The Child before the Court : Judgment, Citizenship, and the Constitution - Barouch, Timothy, 1974- (Book collections on Project MUSE., 2021)
"A study that challenges our notions about citizenship and judgment by considering the place of the "child" in both historical and contemporary legal discourse in landmark cases involving the child's rights to free speech and due process"--